Preclinical evaluation of a TEX101 protein ELISA test for the differential diagnosis of male infertility - Korbakis, Dimitrios (BMC Med, 2017)
BACKGROUND: TEX101 is a cell membrane protein exclusively expressed by testicular germ cells and shed into seminal plasma. We previously verified human TEX101 as a biomarker for the differential diagnosis of azoospermia, and developed a first-of-its-kind TEX101 ELISA. To demonstrate the clinical utility of TEX101, in this work we aimed at evaluating ELISA performance in a large population of fertile, subfertile, and infertile men. METHODS: Mass spectrometry, size-exclusion chromatography, ultracentrifugation, and immunohistochemistry were used to characterize TEX101 protein as an analyte in seminal plasma. Using the optimized protocol for seminal plasma pretreatment, TEX101 was measured by ELISA in 805 seminal plasma samples. RESULTS: We demonstrated that TEX101 was present in seminal plasma mostly in a free soluble form and that its small fraction was associated with seminal microvesicles. TEX101 median values were estimated in healthy, fertile pre-vasectomy men (5436 ng/mL, N = 64) and in patients with unexplained infertility (4967 ng/mL, N = 277), oligospermia (450 ng/mL, N = 270), and azoospermia (0.5 ng/mL, N = 137). Fertile post-vasectomy men (N = 57) and patients with Sertoli cell-only syndrome (N = 13) and obstructive azoospermia (N = 36) had undetectable levels of TEX101 (≤0.5 ng/mL). A cut-off value of 0.9 ng/mL provided 100% sensitivity at 100% specificity for distinguishing pre- and post-vasectomy men. The combination of a concentration of TEX101 > 0.9 ng/mL and epididymis-specific protein ECM1 > 2.3 μg/mL provided 81% sensitivity at 100% specificity for differentiating between non-obstructive and obstructive azoospermia, thus eliminating the majority of diagnostic testicular biopsies. In addition, a cut-off value of ≥0.6 ng/mL provided 73% sensitivity at 64% specificity for predicting sperm or spermatid retrieval in patients with non-obstructive azoospermia. CONCLUSIONS: We demonstrated the clinical utility of TEX101 ELISA as a test to evaluate vasectomy success, to stratify azoospermia forms, and to better select patients for sperm retrieval. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12916-017-0817-5) contains supplementary material, which is available to authorized users.